Acute on chronic liver failure- etiology, clinical profile, prognostic scores: experience from tertiary care centre of eastern India - Behera, Sanatan; Prakash, Vivek; Bajpai, Shivam; Patra, Umesh Chandra; Jena, Sushanta Kumar (International Journal of Research in Medical Sciences, 2021)
Background: Acute on chronic liver failure (ACLF) is a recently recognised entity in chronic liver disease patients. Data regarding ACLF in terms of clinical presentation, etiology of underlying cirrhosis, precipitating factors, prognostic factors are lacking from eastern India. The present study was undertaken to evaluate the above factors along with the assessment of short-term mortality (4 weeks) in patients of ACLF. Methods: In this prospective observational study, 120 patients diagnosed as ACLF were included. A comparison of complications, biochemical profiles and prognostic scores was made between the survivor and non-survivor groups. Results: Of the 120 ACLF patients included, the mean age was 44.9±8.6 years and the male to female ratio was 2.5:1. Common clinical presentations were jaundice (100%), ascites (88.3%), hepatic encephalopathy (60%). The most common etiology for underlying CLD was alcohol (51.7%) followed by chronic hepatitis B (20%) and chronic hepatitis C (15%) infection. Alcohol hepatitis (40%) followed by hepatotropic viral infections (20%) and drug-induced liver injury (15%) were common identifiable precipitating agents. After a follow-up period of 4 weeks, 56 (46.6%) out of 120 patients died. The presence of sepsis, hyponatremia, renal failure, and coagulopathy was significantly associated with high mortality. Mortality was higher among patients having high Chronic liver failure consortium- acute on chronic liver failure (CLIF-ACLF) grade and closely related to the number of organ failures. Conclusions: ACLF is a rapidly progressive syndrome in chronic liver disease patients, having high short-term mortality.